Effects of fertilizers and media on Justicia gendarussa Burm F. cuttings and their biomass - Hamzah, Nur Adnilaila (2012)
Justiciagendarussa is considered as an important medicinal plant species. This species has been used in both traditional and modern medicine practice and has a vast potential to be commercialized in future market. In order to get better growth performance of the plant, several aspect should be considered such as cutting selection, suitability of the media and types of fertilizer. These factors are important to ensure better growth performance thus increase yield and enhance the biomass value.However, little information is available on the growth performance or on the biomass aspect of J. gendarussa. A silvicultural study was conducted with objectives to determine the best media for J. gendarussacutting, the best organic fertilizer for J. gendarussa growth and also to determine the biomass based on various treatments on the cuttings of J. gendarussa.In order to determine the best propagation part of J. gendarussa, the plant was divided into three different cutting parts: shoot, mid-stem and basal part. Cutting from these parts were assigned to four different media of topsoil only, topsoil mixed with treated palm oil mill effluent (POME) at the ratio 1:1, topsoil mixed with POME at the ratio 1:2, and POME only. After four months, the plantlets were transferred into planting site inSeremban, Negeri Sembilan. Three types of organic fertilizers with four different rates were applied according to the experimental design. The fertilizers were wood charcoal, bamboo charcoal and chicken manure and the rates are 0 g, 50g, 100g and 150g. The experimental design used for this study was Randomized Completely Block Design (RCBD) with total of eight replicates. After six month in planting site, the J. gendarussa were harvested to determine its wet and dry weight. Height, crown diameter and stem diameter of the plants were measured and growth increment data was used for statistical analysis. For growth performance in nursery, the data were collected once a week while in planting site the data were collected twice a month. The result indicated that in the nursery stage, the shoot cutting had showed the highest in height, crown diameter and also stem diameter with mean value at 13.09 cm, 12.4 cm and 0.46 cm respectively. The result also indicate that medium of topsoil (1): POME (2) hadthe highest mean value for all parameters with 10.14 cm for height, 10.33 cm for crown diameter and 0.36 cm for stem diameter. For growth performance of J. gendarussa at the planting site, the result showed that there was significant different for interaction between the medium, type of fertilizer and the growth rates. The result also showed that for height parameters, J. gendarussa have the highest mean value of 26.36 cm when cutting at the shoot part and medium consisting of topsoil (1): POME (2) gave the best result with mean height at 33.28 cm. The best fertilizer is chicken manure with application at 150 g which gave the highest mean height of 36.43 cm. For crown diameter of J. gendarussa, the cutting at mid-stem gave the superior result of 9.05 cm. The best medium was topsoil (1): POME (2) which record the mean crown diameter length at 11.73 cm and the best fertilizer for crown diameter was chicken manure with 14.89 cm by application at 100 g. Meanwhile, for the diameter of J. gendarussa, the shoot cutting again gave the biggest mean value of 0.9 cm. However, the best medium was topsoil with mean diameter for J. gendarussaat 1.01 cm. Wood charcoal gave the biggest mean diameter value of J. gendarussa1.35 cm when applied at 150 g. The dry weight was used to determine the biomass value. The results indicated that the leaves and stem portion of J. gendarussa had higher dry weight compared to root part. Cutting at the shoot part had produced mean dry weight of J. gendarussa at 0.6 t/ha with media of topsoil (1): POME (2) had resulted mean dry weight of J. gendarussa at 0.8 t/ha. The result also showed that both chicken manure and bamboo charcoal produced higher dry weight for J. gendarussa which both application resulted at 0.4 t/ha when allotted 1.5 t/ha of either fertilizers. Thus, J. gendarussa can be propagated from shoot cutting with medium consisting of topsoil (1): POME (2). In addition, the best fertilizer to be applied is chicken manure at 150 g.